Ecological and Sanitary Basics of Landscaping of Classrooms and Adjacent Areas - Emilbekova, Dinara; Buranov, Eduard; Abdyrakhmanova, Zhazgul; Umetaliev, Myrzaali; Turdubaeva, Gulsara; Osmonali uulu, Adakan; Manasov, Nasirbek; Zhakyshova, Batima (Research in Ecology, 2025)
The scientific article discusses the principles of ecological landscaping of the classroom related to the creation and development of a safe educational environment. The functions of vertical landscaping of the classroom and the territory, as well as the plants used in it, are defined. The ways of creating the principle of “tieredness” in ecological gardening are determined. The conformity of the measurements of landscaping inside the classroom with the norms of safety of landscaping according to SanPiN KR was determined and their results were presented. In our study, we took the green component of ecological safety as the basis of the educational environment. After all, the ecological landscaping of the educational room is an important and indispensable part of creating a favorable environment for the health of students and the development of complex: aesthetic, ecological culture. Greening plays a decisive role in maintaining a microclimate favorable for health. When plants are properly placed according to safety standards in the classroom and on the territory, they provide shade, reduce dust, kill microorganisms causing infectious diseases and clean the air. Therefore, many species of native plants grown in Central Asia are used for the landscaping of educational buildings.